Evaluating the extent of awareness among a sample of secondary school teachers in the concept of media education and the importance of including it in the school curricula in the Kingdom of Saudi Arabia - Al- Musned, Shada Saleh (Journal of Educational and Psychological Sciences, 2020)
This study aimed to assess the extent to which a sample of male and female teachers at the secondary level in Riyadh perceive the concept of media education and the importance of including it in the school curriculum. To achieve this, the researcher used the descriptive method, and the questionnaire was used as a study tool. As it was distributed to a sample of (128) male and female teachers, the study found that the general tool for teachers and secondary teachers in Riyadh has understood the concept of media education and the importance of including it in the school curricula at an arithmetic average (1.44 out of 3), with an estimate (few), and at the level The two main areas; the field of cognition obtained a general average (1.64), followed by the field of the importance of including media education with an average of (1.24); both are rated (few); Based on the results, the researcher recommended taking advantage of advanced foreign countries in teaching media education, cooperation between the Ministry of Culture and the Ministry of Education in disseminating the culture of media education, its values, and its competencies, and that media education be included as a decision within the plan of colleges of education in universities, and the general education plan.